2016
DOI: 10.1055/s-0036-1592081
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Pituitary Adenomas Presenting as Sphenoid or Clival Lesions: Case Series and Management Recommendations

Abstract: Background An ectopic pituitary adenoma presenting as a clival or sphenoid mass is a rare clinical occurrence that may mislead the clinician and result in unnecessary interventions or potential medicolegal consequences. Here, we present one of the largest multi-institutional case series and review the literature with an emphasis on radiological findings and critical preoperative workup. Methods Retrospective chart review. Results Nine patients were identified with ectopic pituitary adenomas of the sphenoid or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…The patient in our case demonstrated ACTH immunoreactivity but with nonspecific symptoms. Although lack of full-workups of pituitary function, it is similar to a previous case report [ 15 ]. This type of tumor is usually incidentally discovered in routine imaging for other conditions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The patient in our case demonstrated ACTH immunoreactivity but with nonspecific symptoms. Although lack of full-workups of pituitary function, it is similar to a previous case report [ 15 ]. This type of tumor is usually incidentally discovered in routine imaging for other conditions.…”
Section: Discussionsupporting
confidence: 86%
“…EPA may show aggressive behavior. Bone invasion [ 15 ], tumor seeding [ 16 ], and malignant transformations [ 17 19 ] have also been reported in several case series. The mechanism of this aggressive behavior is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally considered that during the development of the anterior pituitary lobe, the incompletely degraded Rathke cleft cyst remnants of the Rathke pouch lead to the formation of EPAs in the nasopharynx, sphenoid, and clivus. 10,11 EPA is rare in China. Zhu et al 5 recorded 14,357 pituitary gland patients in the last 20 years; of these patients, only 14 were diagnosed with EPA (0.098% of all cases), but none of the lesions The postoperative pathological and immunohistochemical results of the tumor tissue in the patient demonstrated that it was an ectopic ACTH-secreting pituitary macroadenoma in the clivus region.…”
Section: Dovepressmentioning
confidence: 99%
“…Extra-sellar or ectopic pituitary adenomas (EPAs) most likely arise from remnants of the embryological migratory path of the pituitary gland [ 1 , 3 , [5] , [6] , [7] ]. EPAs are a rare presentation of pituitary adenomas and have mostly been described in case reports [ 3 , 5 , [8] , [9] , [10] , [11] , [12] ]. Because they are so uncommon, EPAs may be misdiagnosed as other skull lesions such as chordomas, chondrosarcoma, meningioma or astrocytomas [ 3 , 8 ].…”
Section: Introductionmentioning
confidence: 99%